Peningkatan Hasil Belajar Pendidikan Agama Katolik Melalui Model PBL di Kelas IV SD Negeri 1 Tualang - Eventina Manalu; Andarweni Astuti (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to determine the improvement of learning outcomes by using the based learning model in class IV of SD Negeri 1 Tualang. This study used the Classroom Action Research (CAR) method, the population of this study were Catholic students in class IV of SD Negeri 1 Tualang totaling 9 students consisting of 3 males and 6 females. Sampling using purposive sampling and the sample used was class IV totaling 9 students. The results of this study indicate that student learning outcomes using the based learning model are included in the very good category seen that the average post-test score of the best students at the cycle I stage was 85 then increased to 90 in the post-test cycle II and the smallest students at the Cycle 1 stage were 60 then increased to 75. This shows that there is a significant positive influence of the use of based learning on student learning outcomes in the subject of Catholic Religious Education in class IV of SD Negeri 1 Tualang